Perilaku Akhlaqul Karimah Siswa: Survei di SMU UNJ - Latif, Mukhtar (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This research aims at determining the relationships between reading interest, teachers islamic knowledge and Islamic teacherâs performance individually or collectively with the akhlaqul karimah behavior. The research is conducted at SMU Universitas Negeri Jakarta where 90 respondents are selected randomly.